Assessment of Knowledge, Attitude, and Practice on Voluntary Blood Donation in Shkodra City - Gjinaj, Vera Asllani; Shabani, Zamira; Pjetergjokaj, Kristjana (European Scientific Journal, ESJ, 2018)
Blood is a liquid mass that is produced from the bone marrow and it circulates in our body. The only source for donation is by a human. In Shkodra City, the main donation is the family donation and about 400 units are provided by voluntary donation organized by the Albanian Red Cross, Shkodra Branch. These voluntarily donated units go mainly for people suffering with thalassemia. This study is a cross-sectional, transversal, punctual, and descriptive study. It was developed from January – March 2018 in Shkodra region among volunteer blood donors. The people who have been offered as volunteers of blood donation during this period (about one hundred people) have previously completed a standardized closed questionnaire. This questionnaire was self-reported with their permission. All the collected data was analyzed by SPSS version 20 Program.